Poor postnatal weight gain predicts stage 3+ retinopathy of prematurity in very low birth weight infants - Anuk İnce, Deniz; Gülcan, Hande; Hanta, Deniz; Ecevit, Ayşe; Akkoyun, Imren; Kurt, Abdullah; Tarcan, Aylin (The Turkish Journal of Pediatrics, 2013)
Multiple systemic risk factors are associated with retinopathy of prematurity (ROP). We analyzed the role of low weight gain (WG) to predict the development of stage 3+ ROP among preterm infants. This study included 126 newborns with birth weight ≤1500 g and gestational age